IMRAD, synthesis, and hedging within expert academic writing to encourage a world discussion platform - Jumanto Jumanto; Dwi Eko Waluyo; Aris Puji Purwatiningsih; Pulung Nurtantio Andono; Raden Arief Nugroho; Ismarita Ramayanti; Asnul Dahar Bin Minghat (Universitas Syiah Kuala, 2024)
This paper examines IMRAD, synthesis, and hedging within expert academic writing to encourage a world discussion platform and to enhance manuscript writing for internationally reputable journals. The research utilized 25 Quartile-1 Scopus-indexed articles from 25 scholarly journals from 2022 and 2023 publications across different subject areas. Through online searching, observation, and interpretive techniques, the patterns of IMRAD, its synthesis, and the use of hedging within the synthesis were analyzed and identified as crucial elements for creating a manuscript that serves as a world discussion platform. Based on the systematic observation and interpretation of the 25 data sources, the research findings were discussed across three aspects: the IMRAD pattern, synthesis, and hedging. The findings revealed that symmetrical IMRAD patterns were rarely employed by authors of Quartile-1 Scopus-indexed journals, with various patterns being applied and the largest proportion focusing on different aspects. Synthesis was utilized by all authors of the 25 journal articles, and hedging or cautious language was used by most authors. Authors worldwide may benefit from the results of this research when writing manuscripts to be submitted to internationally reputable journals. Additionally, academic writing teachers can use the proposed interpretive model and research results to teach expert academic writing to their students, thus enhancing the quality of student academic writing and enabling the publication of their papers in internationally reputable journals.